Empirical model building data, models, and reality - Thompson, James R. (James Robert), 1938- (Wiley series in probability and statistics, 2011)
"This book presents a hands-on approach to the basic principles of empirical model building through the shrewd mixture of differential equations, computer-intensive methods, and data in a single-volume. It includes a series of real-world statistical problems illustrating modeling skills and techniques that are applicable to a broad range of audiences from applied statisticians to practicing MBAs. It covers models of growth and decay, systems where competition and interaction add to the complexity of the model, and discusses both classical and non-classical data analysis methods, alongside an extended list of more than twenty essential topics. The author also includes numerous exercises, an emphasis on computational finance and Bayesian techniques, and timely discussions of epidemics, quality control, and chaos in a dynamic world"--